2017
DOI: 10.1051/0004-6361/201731256
|View full text |Cite
|
Sign up to set email alerts
|

Breaks in surface brightness profiles and radial abundance gradients in the discs of spiral galaxies

Abstract: We examine the relation between breaks in the surface brightness profiles and radial abundance gradients within the optical radius in the discs of 134 spiral galaxies from the CALIFA survey. The distribution of the radial abundance (in logarithmic scale) in each galaxy was fitted by simple and broken linear relations. The surface brightness profile was fitted assuming pure and broken exponents for the disc. We find that the maximum absolute difference between the abundances in a disc given by broken and pure l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 73 publications
1
12
0
2
Order By: Relevance
“…15 shows that the central intersect abundances (and the intersect abundances at the optical radius) for the cases A and B are in agreement, the mean difference is ∼0.013 dex. This is not surprising since it was found in our previous study that the maximum absolute difference between the abundances in a disk given by broken and pure linear relations is less than 0.05 dex for the majority of galaxies (Pilyugin et al 2017b). The values of the central intersect abundance, the abundance at the optical radius and the radial abundance gradient obtained using the points with galactocentric distances within 0 < R g < 1 will be examined below.…”
Section: Abundance and Abundance Gradientmentioning
confidence: 71%
See 2 more Smart Citations
“…15 shows that the central intersect abundances (and the intersect abundances at the optical radius) for the cases A and B are in agreement, the mean difference is ∼0.013 dex. This is not surprising since it was found in our previous study that the maximum absolute difference between the abundances in a disk given by broken and pure linear relations is less than 0.05 dex for the majority of galaxies (Pilyugin et al 2017b). The values of the central intersect abundance, the abundance at the optical radius and the radial abundance gradient obtained using the points with galactocentric distances within 0 < R g < 1 will be examined below.…”
Section: Abundance and Abundance Gradientmentioning
confidence: 71%
“…where (O/H) * ≡ 12 + log(O/H)(R) is the oxygen abundance at the fractional radius R g (normalized to the optical radius R 25 ), (O/H) * 0 ≡ 12 + log(O/H) 0 is the intersect central oxygen abundance, and grad is the slope of the oxygen abundance gradient expressed in terms of dex/R 25 . The radial abundance gradients within the optical radius in the discs of the majority of spiral galaxies are reasonably well fitted by this relation although in some cases breaks in the radial abundance gradients near the centre or near the optical radius can occur (e.g., Vila-Costas & Edmunds 1992;Edmunds & Pagel 1984;Zaritsky, Kennicutt & Huchra 1994;van Zee et al 1998;Pilyugin 2001Pilyugin , 2003Sánchez et al 2012bSánchez et al , 2014Ho et al 2015;Pilyugin et al 2014aPilyugin et al , 2017bZinchenko et al 2016;Sánchez-Menguiano et al 2016. To examine the influence of a possible break in the radial abundance gradient on the central (intersect) abundance and on the abundance at the optical radius (intersect), the value of the gradient based on the points with galactocentric distances within 0.8 > R g > 0.2 is also obtained for each galaxy.…”
Section: Abundance and Abundance Gradientmentioning
confidence: 81%
See 1 more Smart Citation
“…Additionally, it should be noted that exponential abundance gradients are fitted across the full radial range available by P14, while SM16 and SM18 only fit abundance data that lie in the range 0.2 < r/re < 2.0, in order to exclude potential abundance gradient breaks in the inner and outer parts of the disks. Pilyugin et al (2017) found that the difference between the two approaches is, to first order, negligible.…”
Section: Long Slit Sample Of Spiral Galaxiesmentioning
confidence: 96%
“…Así, las propiedades locales jugarían un rol principal en la determinación de las propiedades integradas y, por consiguiente, de las relaciones globales en general. Pilyugin et al (2017) construyeron mapas de abundancia del oxígeno de los discos de 134 galaxias espirales usando espectroscopía 2D del DR3 del relevamiento CALIFA y examinaron la existencia de un quiebre en la pendiente de los RMPs aplicando dos ajustes a los spaxels analizados, uno lineal puro y otro con una línea quebrada (panel derecho de la Figura 1.5). Encontraron una diferencia entre la pendiente quebrada y la lineal menor al 0.05 dex, sugiriendo que una simple regresión lineal es adecuada, al menos a primer orden, para describir la distribución radial de las abundancias del oxígeno en los discos de galaxias espirales.…”
Section: Metalicidades En La Nueva Eraunclassified